2016
DOI: 10.1016/j.molp.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

ABF2, ABF3, and ABF4 Promote ABA-Mediated Chlorophyll Degradation and Leaf Senescence by Transcriptional Activation of Chlorophyll Catabolic Genes and Senescence-Associated Genes in Arabidopsis

Abstract: Chlorophyll (Chl) degradation is an integral process of leaf senescence, and NYE1/SGR1 has been demonstrated as a key regulator of Chl catabolism in diverse plant species. In this study, using yeast one-hybrid screening, we identified three abscisic acid (ABA)-responsive element (ABRE)-binding transcription factors, ABF2 (AREB1), ABF3, and ABF4 (AREB2), as the putative binding proteins of the NYE1 promoter. Through the transactivation analysis, electrophoretic mobility shift assay, and chromatin immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(223 citation statements)
references
References 95 publications
(156 reference statements)
3
206
0
2
Order By: Relevance
“…Consistent with its trend in our RNA-seq database, BrWRKY65 transcript level increased during senescence, reaching about 4.2- and 3.8-fold of the initial level at day seven and nine, respectively (Figure 4). In addition, as leaf yellowing is due to chlorophyll degradation [29,32,40,41,42,43], and dark-inducible ( DIN ) genes are induced in dark-adapted and senescing leaves [44,45], which have been used previously as markers to characterize senescence-associated responses. Therefore, we further searched the SAG genes in our RNA-seq transcriptome database, and three SAG s such as BrNYC1 (NON-YELLOW COLORING1/Chl b reductase) (XP_009139641.1) and BrSGR1 (STAY-GREEN1) (XP_018512704.1) associated with chlorophyll degradation, and BrDIN1 (XP_009150416.1) were selected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with its trend in our RNA-seq database, BrWRKY65 transcript level increased during senescence, reaching about 4.2- and 3.8-fold of the initial level at day seven and nine, respectively (Figure 4). In addition, as leaf yellowing is due to chlorophyll degradation [29,32,40,41,42,43], and dark-inducible ( DIN ) genes are induced in dark-adapted and senescing leaves [44,45], which have been used previously as markers to characterize senescence-associated responses. Therefore, we further searched the SAG genes in our RNA-seq transcriptome database, and three SAG s such as BrNYC1 (NON-YELLOW COLORING1/Chl b reductase) (XP_009139641.1) and BrSGR1 (STAY-GREEN1) (XP_018512704.1) associated with chlorophyll degradation, and BrDIN1 (XP_009150416.1) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Arabidopsis ETHYLENE INSENSITIVE3 (EIN3) and ORE1/NAC2 establish a network controlling ethylene-induced leaf senescence via directly targeting NYE1 , NYC1 , and PAO [52]. More recently, abscisic acid (ABA)-responsive element (ABRE)-binding TFs ABF2, ABF3, and ABF4 from Arabidopsis are found to speed ABA-mediated chlorophyll degradation and leaf senescence by the trans-activation of NYE1 , NYE2 , NYC1 , PAO , SAG12 , and SAG29 [42]. Collectively, these results imply the existence of a complex regulatory network of chlorophyll degradation and leaf senescence involving multiple TFs.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, VvMYBA7, recently characterized as a regulator of the anthocyanins synthesis in vegetative organs, was up-regulated by ABA but only at the 20 h time-point, suggesting its direct induction by ABA, but not its participation to the ripening program (Matus et al, 2017). The role of ABA in down-regulating photosynthesis under stressful conditions, such as drought, salinity or low temperature, and during developmental processes, such as senescence (Lee et al, 2004; Yang et al, 2011; Gao et al, 2016), has been extensively described. It is not surprising then that at 44 h the functional enriched categories within the down-regulated genes involve different aspects of the photosynthetic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…More recent study found that chlorophyll degradation was also mediated by abscisic acid. Some genes that regulate the chlorophyll degradation in Arabidopsis had been described, including NYE1 and STAY GREEN genes (Gao et al 2016). Chlorophyll degradation is a crucial process during leaf senescence and fruit ripening because it helps plants to recycle nitrogen and other nutrients (Hortensteiner 2006).…”
Section: Effects Of Elf-emf On Chlorophyll and Carotene/xanthophyll Cmentioning
confidence: 99%